Nonlinear transition radiation of the modulated electron beam from the sharp vacuum-plasma border - Anisimov, I.O.; Kelnyk, O.I.; Tyazhemov, V.K. (Вопросы атомной науки и техники, 2003)
The transition radiation of the radially unbounded modulated electron beam on the sharp vacuum-isotropic plasma boundary is studied up to quadratic nonlinearity approximation. Solution for the second harmonic radioemission and stationary forced fields is considered in details.